2017
DOI: 10.1016/j.powtec.2017.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Breaking pharmaceutical tablets with a hole: Reevaluation of the stress concentration factor and influence of the hole size

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. This is an author-deposited version published in: https://sam.ensam.eu Handle ID

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…For the application of the generalized Hiestand's approach, a special set of flat faced Euro B tooling was used as described previously [20,27]. These tooling made it possible to obtained a so-called flattened geometry.…”
Section: Tablet Compactionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the application of the generalized Hiestand's approach, a special set of flat faced Euro B tooling was used as described previously [20,27]. These tooling made it possible to obtained a so-called flattened geometry.…”
Section: Tablet Compactionmentioning
confidence: 99%
“…As described elsewhere [20], the holes in the tablets were inserted using a drill Micromot 50 E/EF (PROXXON S.A., Luxembourg). Three drill diameters (0.5, 0.8 and 1 mm) were used to make the holes.…”
Section: Tablet Machiningmentioning
confidence: 99%
See 1 more Smart Citation
“…From these, 31.3% deal with the effect of punch shape [ 61 , 74 , 79 , 82 , 85 ]. The second most studied aspect (22.2% of the total) is the stress/strain distribution in the tablet during mechanical strength testing [ 65 , 81 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. From these, 40% deal with the effect of tablet shape and studied crack propagation [ 89 , 90 , 92 , 93 ].…”
Section: Application Of Fea Modelling For Pharmaceutical Tabletsmentioning
confidence: 99%
“…Croquelois et al (2017) [ 86 ] reevaluated the stress concentration factor (SCF) in the case of cylindrical and flattened tablets [ 81 ] with holes, during the diametral compression test, with the aid of FEA; 11-mm tablets were tested for two different materials: acetaminophen ( = 4.4 GPa, = 0.25) and spray dried lactose ( = 3.7 GPa, = 0.23). It was reported that the value of SCF was nearly independent of the hole size when the ratio of the hole and the tablet diameters was less than 0.1.…”
Section: Application Of Fea Modelling For Pharmaceutical Tabletsmentioning
confidence: 99%